Retrospective analysis of indications for termination of pregnancy. (3rd April 2019) - Ozyuncu, Ozgur; Orgul, Gokcen; Tanacan, Atakan; Aktoz, Fatih; Guleray, Naz; Fadiloglu, Erdem; Beksac, Mehmet Sinan
Abstract: This is a retrospective study of 139 termination of pregnancies (TOPs) between November 2015 and November 2017 to demonstrate the indications. We have shown that 60.4%, 34.5% and 5% of the terminations were performed because of genetic disorders, foetal or obstetrical problems, and maternal causes, respectively. Congenital abnormalities (43.8%), anhydramniosis (17.2%) and chromosomal abnormalities (15.1%) were the most frequent causes of the TOPs. The central nervous system seemed to be the most frequent indicator found in our study. The critical finding is the presence of nine (6.4%) terminations because of foetal reasons beyond the 24th gestational week. A vaginal termination occurred in 91.4% of cases, whereas a hysterotomy was performed in 8.6% of the cases. Previous uterine surgery was the most significant risk factor for a hysterotomy. Knowing the foetal indications is essential to know the aetiological and medico-legal backgrounds of the TOPs for better planning and medical counselling. Impact statement: What is already known on this subject? Congenital anomalies are most common cause of termination of wanted pregnancies. Terminations beyond 24 weeks are also evaluated as unethical and create an ethical concern. The legal limitations differ between countries in terms of the legal limit in pregnancy for terminations. What do the results of this study add? We have demonstrated the congenital anomalies are the most common reason for pregnancy terminations after excluding fetal demise and unwanted pregnancies. We also showed that congenital anomalies and chromosomal abnormalities are most common indications for terminations of pregnancies beyond 24 weeks. The legal arrangements related to the termination of pregnancies in Turkey are described. Prior uterine surgery is a significant risk factor for hysterotomies in the termination of pregnancies. What are the implications of these findings for clinical practice and/or further research? It is critical to know the aetiological background of termination of pregnancies for better planning and consultation.